1983
DOI: 10.1177/00220345830620021801
|View full text |Cite
|
Sign up to set email alerts
|

The Acid Pattern in Human Dental Plaque

Abstract: Lactic and volatile acids in standardized plaque samples from 11 subjects have been estimated by means of HPLC before and after exposure to sucrose in vivo. Total acid differed considerably between subjects, but the ratio of acids estimated within the plaque from different persons did not vary significantly. The time-dependent acid pattern following sucrose rinsing allowed the plaque samples to be divided into two groups: one showing only small changes in total acid production; and the other exhibiting a disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…The results for plaque acids are in agreement with the previously reported range of these acids (17-20.5 nmol/ mg for lactate, 6-12.3 nmol/mg for acetate, and 3-11.0 nmol/mg for propionate) [Distler and Kröncke, 1983;Oliveby et al, 1990;Simone et al, 1992]. The slightly higher concentrations for lactate in the current study are probably caused by the differences in subject population, and the plaque sampling technique.…”
Section: Discussionsupporting
confidence: 93%
“…The results for plaque acids are in agreement with the previously reported range of these acids (17-20.5 nmol/ mg for lactate, 6-12.3 nmol/mg for acetate, and 3-11.0 nmol/mg for propionate) [Distler and Kröncke, 1983;Oliveby et al, 1990;Simone et al, 1992]. The slightly higher concentrations for lactate in the current study are probably caused by the differences in subject population, and the plaque sampling technique.…”
Section: Discussionsupporting
confidence: 93%
“…The acid/anion results from this study are similar to those reported by Geddes [1975], Vratsanos et al [1979] and Distler and Kroncke [1983], who have analysed pooled plaque from fasted subjects before and after sucrose rinsing. In the present study, like those cited above, it was found that the lactic acid exhibited a steep in crease following a sucrose rinse.…”
Section: Discussionsupporting
confidence: 90%
“…The two meth ods used to test the composition of the de posits which formed on the appliance were acid/anion profile analysis and microbiological assessment. These tests were chosen because the changes in or ganic acid levels of fasted plaque after ex posure to sucrose have been investigated thoroughly [Distler and Kroncke, 1983;Geddes, 1975;Geddes and Weetman, 1983;Gilmour et al, 1976] and the bacte ria normally present in 7-to 9-day-old dental plaque have been well character ised [Ritz, 1967],…”
mentioning
confidence: 99%
“…Kuhn and Wilson (1985) mentioned that the dissolution of glass-ionomer and silicate cements included three steps: (1) surface wash-off, (2) diffusion in the solid state, and (3) surface corrosion. We reported in our previous article that the dissolution of glass-ionomer cements in an acidic acetate-buffer solution was controlled by the diffusion of species through the cement matrix, and that the elution of species was in proportion to the square root of immersion time.The mouth contains more organic acids than acetic acid (Distler and Kroncke, 1983). We reported that the H' ion concentration and the formation constants for soluble complexes between the acid anions and metal cations in the set cement controlled the degree of the erosion of a glass-ionomer cement in organic-acid solutions (Matsuya et al, 1984).…”
mentioning
confidence: 99%